Experimental and modeling study of hydrogen production from catalytic steam reforming of methane mixture with hydrogen sulfide. (7th September 2015) - Sadooghi, Parham; Rauch, Reinhard
Abstract: Experimental and theoretical studies of steam methane reforming reactions with different amount of hydrogen sulfide in the feed gas are presented. A two dimensional pseudo-heterogeneous model is developed to simulate methane steam reforming reactions in a packed bed tubular reactor. This model is based on mole and energy balance equations for the catalyst and the fluid phases. Attention is given to the analysis of sulfur negative effects on reforming process. A parametric study is done and effects of different steam to carbon ratios, space velocities, temperatures and different amount of sulfur on methane conversion and temperature distribution within the reactor are investigated. The results are verified comparing to the experimental results. It is shown that even presented in the gas at very low concentration levels (ppm), sulfur drastically decreases the conversion of methane. The obtained results play a key role in design and optimization of an actual reactor. Highlights: Steam reforming of methane mixture with hydrogen sulfide is modeled. Experimental and modeling results are carefully compared. Effects of different processing conditions are investigated. Sulfur negative effects on reforming reactions are discussed.